Training practices for professionals and technical staffs in selected menufacturing sector - Mustafa, Munauwar; Hasan, Hasnizam; Kassim, Mohd Shah; Ghazali, Zahiruddin (2000)
The objective of this study was to describe the training practices for professionals and technical staffs in the four selected industries in the manufacturing sector in Malaysia. The population frame was based on the directory of manufacturers throughout the country provided by MIDA (MIDA, 1996). Due to the large number of companies and limited budget, this study will only focus on four industries i.e the electrical and electronics industry, chemical and chemical products industry. From the 1340 companies, 60 companies were identified as respondents and were chosen by using the stratified random sampling method.Interviews were structured through the use of a form and were conducted with the appropriate staff members of the companies who are in-charge of the training activities.Findings of this study on the training objectives, the importance of training and development, influence on budget by various job categories, the training need assessment analysis, the training needs assessment data gathering methods, the training types, training methods, training providers, training venues, instructional media and the training evaluation supported findings from previous researches even though those researches did not specifically focus on the training of professionals and technical staffs in the manufacturing sector.